A simplified fluid resuscitation formula for burns in mass casualty scenarios: Analysis of the consensus recommendation from the WHO Emergency Medical Teams Technical Working Group on Burns. Issue 8 (December 2021) - Leclerc, Thomas; Potokar, Tom; Hughes, Amy; Norton, Ian; Alexandru, Calin; Haik, Josef; Moiemen, Naiem; Almeland, Stian Kreken
Highlights: Fluid resuscitation for burns is usually started based on burned surface area and weight, then adjusted on patient response. For mass burn casualties, resource scarcity and needed expeditiousness without burn expertise make this initially impracticable. Above 20%TBSA in mass casualties, the WHO Technical Working Group on Burns recommends 100 mL/kg body weight/24 h initially, p.o. below 40% TBSA and i.v. above. This formula reasonably agrees with TBSA-dependent resuscitation guidelines in most patients but would underresuscitate burns above 60%TBSA. In burn disasters, the simplicity of the formula, its usability and its safety should outweigh its limits and help improve overall outcomes. Abstract: Background: Burn fluid resuscitation guidelines have not specifically addressed mass casualty with resource limited situations, except for oral rehydration for burns below 40% total body surface area (TBSA). The World Health Organization Technical Working Group on Burns (TWGB) recommends an initial fluid rate of 100 mL/kg/24 h, either orally or intravenously, beyond 20% TBSA burned. We aimed to compare this formula with current guidelines. Methods: The TWGB formula was numerically compared with 2–4 mL/kg/%TBSA for adults and the Galveston formula for children. Results: In adults, the TWGB formula estimated fluid volumes within the range of current guidelines for burns between 25 and 50% TBSA, and a maximal 20 mL/kg/24 h difference in the 20–25% and the 50–60% TBSA ranges. In children, estimated resuscitation volumes between 20 and 60% TBSA approximated estimations by the Galveston formula, but only partially compensated for maintenance fluids. Beyond 60% TBSA, the TWGB formula underestimated fluid to be given in all age groups. Conclusion: The TWGB formula for mass burn casualties may enable appropriate fluid resuscitation for most salvageable burned patients in disasters. This simple formula is easy to implement. It should simplify patient management including transfers, reduce the risk of early complications, and thereby optimize disaster response, provided that tailored resuscitation is given whenever specialized care becomes available.